Land Erosion - Sitholey, B. S. (Indian Forester, 1949)
Control of erosion by Nature will prove ineffective unless human activities contributing to erosion are given up. The land has its limitations and though its yield may be scientifically increased, the overworked land is bound to go into decay. A symbiotic relationship, taking as well as giving, is essential between man and land. From the agricultural standpoint, erosion occurs through rain, rivers, frost, wind and sun. Cover of land by vegetation is the main single protective measure, involving creation of forest belts and growing of detached trees. Terracing, strip-cropping, and contour-ridging are essential. River erosion can be countered by strengthening river banks with soil-binding plants. Floods can be checked by diverting floor-water into escape channels, from which it can gradually drained off. Over-grazing needs to be stopped, and the live-stock reduced in number. Other sources of food, not dependent on land, should be exploited, specially river fist. Fist is destroyed in large numbers by sewage and industrial wastes discharged into rivers. Manure contents could be extracted fron sewage and profitable by-products recovered from industrial wastes.